New Imported Inputs, Wages and Worker Mobility - Italo Colantone; Alessia Matano; Paolo Naticchioni (Institute of Labor Economics (IZA), 2019)
We study how firms and industries adjust to increasing international trade in intermediate inputs. In particular, we provide a comprehensive assessment of the effects of new imported inputs on wage dynamics, on the skill-composition of the labor force, on worker mobility, and on assortative matching between firms and workers. We employ matched employer-employee data for Italy, over 1995-2007. We complement these data with information on the arrival of new import-ed inputs at the industry level. We find new imported inputs to have a positive effect on average wage growth at the firm level. This effect is driven by two factors: (1) an increase in the white-collar/blue-collar ratio; and (2) an increase in the average wage growth of blue-collar workers, while the wage growth of white collars is not significantly affected. The individual-level analysis reveals that the increase in the average wage of blue collars is driven by the displacement of the lowest paid workers, while continuously employed individuals are not affected. We estimate the unobserved skills of workers following Abowd et al. (1999). We find evidence that new imported inputs lead to a positive selection of higher-skilled workers, and to an increase in the degree of positive assortative matching between firms and workers.
Keywords: J01; J31; F14; 330; matched employer-employee data; wages; new imported inputs